Economic Education Research: Theoretical Foundations and Empirical Research, Directions and Trends in the Past Decades - Celeste Varum; Abigail Ferreira; Ana Breda (Journal of Social Science Education, 2012)
With the crisis that has taken place from 2007 became clear that knowledge about economic issues is essential to address the increasingly complex day-by-day dynamics. Not surprisingly the theme of economics education enjoyed a clear revival, reflected also in the academic publications. This paper systematizes the existing literature, which is a necessary step in developing the field. For researchers, this review also supports the definition of a future research agenda. For practitioners, it provides an outline of the literature in this area, raising awareness to the diverse aspects of economic literacy.